Empresas ‘zumbis’ nos mercados emergentes: causas, consequências e leis de falências - Granzotto, Alberto (2024)
The term ‘zombie’ refers to companies whose financial expenses from debts are higher than the profits they can produce. The number of ‘zombie’ companies has been growing worldwide since the early 2000s, especially in emerging markets, where it is observed that there is an ideal environment for their survival. Based on this context, this thesis sought to analyze the institutional determinants and the economic-financial consequences of ‘zombie’ companies in 25 emerging markets between 2000 and 2021. In addition, it sought to analyze whether the Bankruptcy Laws in force in these countries influence their fractions of ‘zombie’ companies. To achieve these objectives, an exploratory-descriptive research based on quantitative methods was used, where difference-in-differences and multilevel modeling were used. As a result, this thesis identified that the 'zombie' fractions in emerging markets represent 7%, if considering the static 'zombie' metric, and 6% if considering the dynamic 'zombie' metric. Among the emerging markets, Brazil was the country that presented the largest 'zombieland' given that its 'zombie' fraction is approximately 2.3 times larger than the average for emerging markets. As for institutional determinants, it was identified that 'zombies' are positively impacted by interest rates, real GDP, company size (small fraction), financial development, economic freedom and English legal origin, and negatively by real GDP growth, creditors' rights and debt enforcement. On the other hand, it was shown that this ‘zombie’ status generates economic consequences, reducing labor productivity and causing disinflation and, as a financial consequence, companies invest less, are more leveraged, retain less cash, are less likely to pay dividends, innovate less, increase their debt maturities and generate higher levels of risk. In addition, it was also identified that as the ‘zombie’ fractions grow, their non-zombie peers are also affected, both economically and financially. Finally, it was shown that bankruptcy laws in emerging markets can be an efficient mechanism for dealing with ‘zombie’ companies, as they improve the bankruptcy process, as reported specifically for China, Brazil and India. In aggregate, it was shown that post-reform of bankruptcy laws reduces the company's propensity to become a static and dynamic ‘zombie' by 21% and 41%, respectively. These propensities translate into a 2% and 1% decrease in the static and dynamic zombie fractions in emerging markets. This result highlights the importance of bankruptcy laws, as these decreases counterbalance the rapid growth of zombielands, as this decrease represents approximately 28% fewer static zombies or 33.33% fewer dynamic zombies.